Brain intraventricular injection of amyloid-β in zebrafish embryo impairs cognition and increases tau phosphorylation, effects reversed by lithium. - Laura Roesler Nery (Public Library of Science (PLoS), 2014)
Alzheimer's disease (AD) is a devastating neurodegenerative disorder with no effective treatment and commonly diagnosed only on late stages. Amyloid-β (Aβ) accumulation and exacerbated tau phosphorylation are molecular hallmarks of AD implicated in cognitive deficits and synaptic and neuronal loss. The Aβ and tau connection is beginning to be elucidated and attributed to interaction with different components of common signaling pathways. Recent evidences suggest that non-fibrillary Aβ forms bind to membrane receptors and modulate GSK-3β activity, which in turn phosphorylates the microtubule-associated tau protein leading to axonal disruption and toxic accumulation. Available AD animal models, ranging from rodent to invertebrates, significantly contributed to our current knowledge, but complementary platforms for mechanistic and candidate drug screenings remain critical for the identification of early stage biomarkers and potential disease-modifying therapies. Here we show that Aβ1-42 injection in the hindbrain ventricle of 24 hpf zebrafish embryos results in specific cognitive deficits and increased tau phosphorylation in GSK-3β target residues at 5dpf larvae. These effects are reversed by lithium incubation and not accompanied by apoptotic markers. We believe this may represent a straightforward platform useful to identification of cellular and molecular mechanisms of early stage AD-like symptoms and the effects of neuroactive molecules in pharmacological screenings.